Design and fabrication of rempeyek making machine / Ahmad Nor Aafif Saharrudin - Saharrudin, Ahmad Nor Aafif (2023)
Rempeyek is a common traditional cake that are origin from Indonesia and are now widely eaten by people from Malaysia. Rempeyek are usually make by people at home to serve the guest during any feast or celebration. The problem occur by this rempeyek is that it usually served in a large quantity since it gets a good response from the guest. People like rempeyek so much. However, due to this, it requires many efforts, time and energy to make rempeyek in a large quantity. So, it requires a machine that can produce rempeyek in a large quantity in a short period of time. The objective of this project is to design a machine that can produce rempeyek with higher productivity and to develop a fully automatic rempeyek machine that can operate without using a lot of time and energy. The results are expected to should be stable to carry the load of the flour, anchovies and peanuts. The material of the machine has to withstand heat so that the heat process can be conduct efficiently. The time of the machine to put the ingredient should be accurate with the position of the molding tray so that the ingredient can be put to the baking tray with the right amount of flour, anchovies and peanuts. The machine should be running smoothly during the process of making the rempeyek so that it can be use in the industry and helps people in making a good rempeyek